Pattern of tissue deposition, gain and body composition of Nellore, F1 Simmental × Nellore and F1 Angus × Nellore steers fed at maintenance or ad libitum with two levels of concentrate in the diet - Oliveira, Ivanna Moraes de; Paulino, Pedro Veiga Rodrigues; Marcondes, Marcos Inácio; Valadares Filho, Sebastião de Campos; Detmann, Edenio; Cavali, Jucilene; Jucilene, Rafael Mezzomo; Duarte, Marcio de Souza (Revista Brasileira de Zootecnia, 2011)
Sixty 18-month-old steers (20 Nellore, 20 F1 Simmental × Nellore and 20 F1 Angus × Nellore with average body weight of 265.6±6.4 kg; 325.3±4.7 kg and 324.6±6.0 kg, respectively) were used. The effects of feeding regime and genetic group on physical carcass composition, empty body composition, composition of the gain, as well as the pattern of tissue deposition were evaluated in this trial. The interaction between genetic group and feeding regime was not significant for any variable evaluated. Animals fed at the maintenance level produced carcass with larger proportions of bones and muscle than the animals fed ad libitum and Nellore animals had larger muscle portion and smaller adipose tissue portion on the carcass than the crossbred animals. Nellore animals and those fed at maintenance had smaller amount of total fat in the carcass than the crossbred animals and those fed ad libitum, respectively. Fat was deposited more pronouncedly in the intermuscular depot, followed by the visceral depot. The rate of deposition of the carcass tissues was smaller in the Nellore animals and in the animals fed the diet with concentrate allowance equivalent to 1% body weight (except for subcutaneous fat tissue), when compared with the crossbred animals and those fed the diet with 2% BW on concentrate, respectively. The rate of fat deposition on the visceral depot was larger in the F1 Angus × Nellore animals and on those fed the 2% of BW of concentrate diet when compared with F1 Simmental × Nellore animals and those fed the diet with the lowest concentrate allowance (1% BW).
Keywords: Empty body gain; Physical gain composition; Visceral fat